Hajj and Umrah during Pandemic Covid-19: The Case of Indonesia - Bramayudha, Airlangga (Nursyam Center, 2023)
Hajj and Umrah are included in the main worship in Islam. Although the ritual is more prominent, there is no doubt that the Hajj and Umrah pilgrimages to Makkah and trips to Medina are commonly accepted as religious events as well as the most important halal tourism in the life of a Muslim. When viewed from the time that has been running for centuries and the total number of participants and the countries of the world that are involved, it is not an exaggeration if Hajj and Umrah can be called as one of largest travel and event in the world. The Covid-19 Pandemic that lasted from the end of 2019 until 2022, has caused a far-reaching impact. There are restrictions everywhere on gathering activities as a result of health and safety protocol policies. No exception for the Hajj and Umrah. Indonesia as a country with the most Muslim population in the world is certainly significantly affected, namely by the cancellation of the delivery of Pilgrims in 2020 and 2021. Likewise, the delivery of Umrah pilgrims had been in a vacuum for months. This article describes what happened starting from the reasons for the cancellation, chronology, the impact and strategic solutions carried out by the Indonesian government and the responses by stakeholder of Hajj and Umrah in Indonesia.